A Historical Inquiry into Early Kurdish-Israeli Contacts:The antecedents of an alliance. Issue 4 (2nd October 2018) - Abramson, Scott
ABSTRACT: This study traces the progress of the contacts between Israelis and Kurds—two non-Arab regional minorities intent on self-government and encircled by enemies—in their earliest stage of development, from the two peoples' first flirtations to the preliminaries of the Israeli-Kurdish entente against Baghdad in the 1960s and 1970s. Irregular in occurrence and anticlimactic in outcome, these early contacts unfolded over three decades in the form of unrequited overtures, dud proposals for cooperation, and stillborn bids for an alliance. Yet for all of these dead-ends, the path along which these early contacts proceeded was, as this article establishes, pursued by the very same Israelis and Kurds, impelled, in turn, by the very same strategic logic, that would lead the two peoples in due course into an alliance.